Analysis of Evolutionary Processes of Species Jump in Waterfowl Parvovirus - Fan, Wentao; Sun, Zhaoyu; Shen, Tongtong; Xu, Danning; Huang, Kehe; Zhou, Jiyong; Song, Suquan; Yan, Liping (Frontiers in Microbiology, 2017)
Waterfowl parvoviruses are classified into goose parvovirus (GPV) and Muscovy duck parvovirus (MDPV) according to their antigenic features and host preferences. A novel duck parvovirus (NDPV), identified as a new variant of goose parvovirus (GPV), is currently infecting ducks, thus causing considerable economic loss. This study analyzed the molecular evolution and population dynamics of the emerging parvovirus capsid gene to investigate the evolutionary processes concerning the host shift of NDPV. Two important amino acids changes (Asn-489 and Asn-650) were identified in NDPV, which may be responsible for host shift of NDPV. Phylogenetic analysis indicated that the currently circulating NDPV originated from the GPV lineage. The Bayesian Markov chain Monte Carlo (MCMC) tree indicated that the NDPV diverged from GPV approximately 20 years ago. Evolutionary rate analyses demonstrated that GPV evolved with 7.674×10−4 substitutions/site/year, and the data for MDPV was 5.237×10−4 substitutions/site/year, whereas the substitution rate in NDPV branch was 2.25×10−3 substitutions/site/year. Meanwhile, viral population dynamics analysis revealed that the GPV major clade, including NDPV, grew exponentially at a rate of 1.717 year−1. Selection pressure analysis showed that most sites are subject to strong purifying selection and no positively selected sites were found in NDPV. The unique immune-epitopes in waterfowl parvovirus were also estimated, which may be helpful for the prediction of antibody binding sites against NDPV in ducks.